The effect of argon plasma coagulation on surgical suture material - V. F. Bezhenar; О. А. Ivanov; Р. М. Palastin; Е. К. Deriy; G. Yu. Yukina; Е. G. Sukhorukova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. In modern surgery, there are many types of different energy used to achieve hemostasis; one of them is the energy of argon plasma coagulation. However, the impact of energy affects not only the bleeding site; it also affects the stitches lying nearby the source of bleeding. The instructions for the use of a suture material or a coagulation tool do not describe the changes that may occur when they interact. A review of the literature found a small number of publications devoted to changes in the physical properties of suture material when exposed to it. This information is not sufficient to predict the effects of argon plasma coagulation energy on the suture material and, as a result, on wound healing or the quality of the postoperative scar.The objective was to determine changes in the biodestructive properties of synthetic absorbable suture materials with argon plasma coagulation in an in vivo experiment.Methods and materials. In the experimental study, the results of biodegradation of monofilament and polyfilament sutures after exposure to argon plasma coagulation energy were analyzed in comparison with control samples in the body of laboratory mice.Results. It can be unequivocally stated that the effect of argon plasma coagulation energy has an effect on the rate of biodegradation of both monofilament and polyfilament synthetic filaments implanted in muscle tissue.Conclusions. Suture material exposed to argon plasma coagulation may not meet the terms of partial or full biodegradation stated by the manufacturer, which may affect the quality of scar formation.